Segmentation, targeting and positioning analysis using k-means clustering model: A case study of the laptop market in Indonesia - Saputra, Tubagus Chandra; Fadhilah, Savira Maghfiratul; Mangkuto, Shidiq Umar; Heikal, Jerry (Trigin Publisher, 2024)
In Indonesia's rapidly evolving laptop market, understanding consumer preferences is crucial for maintaining competitiveness. This study employs the K-Means Clustering algorithm to segment the laptop market based on variables such as age, income, expenditure, laptop price, main usage, and selection criteria. Data were collected from 271 respondents in the Jabodetabek area through an online survey. The analysis identified six distinct customer clusters: Edu-Tech Enthusiasts, Executive Civil Servants, Gov-Corp Society, Steady State Officials, Corporate Climbers, and Emerging Entrepreneurs. Each cluster exhibits unique characteristics and preferences, including preferred brands and price ranges. The findings emphasize the importance of targeted marketing strategies tailored to the specific needs of each segment. By leveraging these insights, laptop producers can optimize product offerings, pricing strategies, and promotional campaigns to enhance market share, customer loyalty, and profitability in Indonesia's competitive laptop industry.